Analysis the Effects of Games on Cognitive Activity of Late Adolescents Using the Electroencephalogram with the K-Nearest Neighbor Method - Azhari, Ahmad; Swara, Ajie Kurnia Saputra (Signal and Image Processing Letters, 2020)
The influence of violent video games on child development continues to be a polemic, Various pros and cons also color this problem, because in adolescence not only adopt cognitive abilities in learning activities, but also various strategies related to managing activeness in learning, playing and socializing to improve cognitive abilities.  Adolescents who are addicted to online games are included in the three criteria set by WHO (Word Health Organization), namely that they need games with symptoms of withdrawing from the environment, losing control, and not caring about other activities (Santoso and Purnomo, 2017).  The purpose of this study is to analyze the cognitive activity of late adolescence between learning and playing games and knowing that games can have a good or bad impact on the cognitive activity of adolescents. The application of the K-Nearest Neighbor method to the system created can classify with prediction results on the influence of games on the cognitive activity of adolescents using Electroencephalogram (EEG) data and can also provide information in the form of new predictions on the respondent data obtained. The results of the analysis resulted in a percentage of accuracy in the game stimulus data of 80%, and in the cognitive stimulus data, namely SPM, it got an accuracy of 80% using the same K value in both stimuli, namely 1, 6, and 7. While the expert results on the system the percentage of superior but addicted respondents was 63.3% and the percentage of respondents who were average but addicted was 36.6% with a correlation rate between Games and SPM of 0.089822409. Based on the results of this study, it can be concluded that the percentage obtained from the comparison of the results of the expert to the results of the system and the comparison of the system itself does not have the influence of games on cognitive activity in late adolescence.